Understanding the Uncanny: The Effects of Human Similarity on Aversion towards Humanlike Robots - Strait, Megan. (2017)
Abstract: Towards facilitating their reception by and communication with human interactants, robots intended for social contexts are often designed with explicit humanlike attributes. However, observation of an "uncanny valley" - a phenomenon in which certain humanlike entities provoke aversion - has lead some to caution against this practice. Substantial evidence supports both of these contrasting perspectives on the anthropomorphic design of social robots. Yet, owing to outstanding empirical limitations and theoretical disputes, the un- canny valley - the nature of its e ects, the underlying mechanisms, and even its existence - remains poorly understood. Across three experiments, we thus explored the relationship between human similarity and people's aversion towards robots via manipulation of the agents' appearances for both robots (Studies 1-3) and human individuals (Study 3). Here, not only do we establish an uncanny valley in the design space of existing social robots, but moreover, we demonstrate that this valley provokes avoidance (Studies 1-3). Countering a common critique, our ndings additionally suggest that the valley is robust to exposure (Studies 2-3). Specifically, while pre-exposure in uences participants' aversion, it did not attenuate participants' aversion towards valley agents (Study 2). Similarly, we found no meaningful relationship between pre-existing attitudes towards robots and par-ticipants' aversive responding (Study 3). Further manipulation of the agents' appearances (Study 3) suggests, instead, that this valley e ect is driven by inconsistent realism and category uncertainty. Speci cially, in contrast to en- counters with humanlike but prototypic agents, encounters with agents with salient atypicalities (e.g., a robot with highly humanlike head), as well as di cult-to-categorize agents (e.g., an android robot), elicited signi cant aver- sion. The present ndings further our understanding of the complex - but im- pactful - relationship between human similarity and aversion towards robots, while also identifying additional research questions for future exploration.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Psychology.; Advisor: Heather Urry.; Committee: Malte Jung, Wendy Ju, Keith Maddox, and Jessica Remedios.; Keywords: Robotics, Cognitive psychology, and Social psychology.